Cryptanalysis and improvement of a block cryptographic scheme based on logistic map - YANG Ji-yun; LIAO Xiao-feng; XIAO Di; DENG Shao-jiang (Tongxin xuebao, 2008)
Through analyzed of an improved chaotic block cryptographic scheme, it was found that this scheme behaves as a stream cipher indeed and generated keystream is independent with plaintext. By means of chosen plaintext attack, the keystream used can easily be recovered with little computing. The algorithm a chosen plaintext attack was proposed and validated by experiment. In order to avoid the flaw, a remedy which makes keystream dependent with plaintext though ciphertext feedback was suggested while keeping all the merits of the original cryptosystem.